Alcohol use before sex and HIV acquisition: a longitudinal study in Rakai, Uganda - Zablotska, Iryna B.; Gray, Ronald H.; Serwadda, David; Nalugoda, Fred; Kigozi, Godfrey; Sewankambo, Nelson; Lutalo, Tom; Wabwire-Mangen, Fred; Wawer, Maria (Aids, 2006)
Alcohol abuse is a major public health problem and is associated with sexually transmitted infections, but the association with HIV is unclear [2]. Alcohol use is common, and disinhibition as a result of alcohol may precipitate and reinforce sexual risk-taking [2–13]. Two cross-sectional studies in Uganda have suggested associations between alcohol use, risk behaviors and prevalent HIV infection [12,14]. However, there are no prospective studies of alcohol use in conjunction with sex and HIV acquisition. We used data from a population based cohort in Rakai, Uganda, to determine whether alcohol use before sex was associated with the risk of HIV acquisition, and risk behaviors.
Keywords: Alcohol; HIV; risk behaviors; Uganda